Comparative Evaluation of Anti-Inflammatory Activity of Curcuminoids, Turmerones, and Aqueous Extract of Curcuma longa - Ashish Subhash Bagad; Joshua Allan Joseph; Natarajan Bhaskaran; Amit Agarwal (Hindawi Limited, 2013)
Curcuma longa is widely known for its anti-inflammatory activity in traditional system of medicine for centuries and has been scientifically validated extensively. The present study was conducted to evaluate the anti-inflammatory activity of curcuminoids and oil-free aqueous extract (COFAE) of C. longa and compare it with that of curcuminoids and turmerones (volatile oil), the bioactive components of C. longa that are proven for the anti-inflammatory potential. The activity against inflammation was evaluated in xylene-induced ear edema, cotton pellet granuloma models in albino Swiss mice and albino Wistar rats, respectively. The results showed that COFAE of C. longa at three dose levels significantly (P≤0.05) inhibited inflammation in both models, as evidenced by reduction in ear weight and decrease in wet as well as dry weights of cotton pellets, when compared to the vehicle control. The COFAE of C. longa showed considerable anti-inflammatory effects against acute and chronic inflammation and the effects were comparable to those of curcuminoids and turmerones.